PENGARUH SUHU DAN VOLUME GAS KERJA TERHADAP DAYA KELUARAN PEMBANGKIT LISTRIK TENAGA TERMAL SURYA MENGGUNAKAN MESIN STIRLING - Rizki Pratama Putra; Hasna Satya Dini; Novi Gusti Pahiyanti (Sekolah Tinggi Teknik - PLN, 2018)
This research aims to investigate the influence of the temperature and the volume of stirling engine working gas on the power output of the solar thermal power plant which uses stirling engine. The methods used in this study are literature review on mathematical model of the system, the observations of the working stirling engine directly to see optimization opportunity, and simulation using simulink to see the output of the plant. The result obtained in this study are ; in general, system performance is strongly influenced by the temperature of the heating plate which is directly related to the working temperature of the gas. The heater plate temperature value is proportional to the output power provided, the higher the temperature of the heater plate, the greater power output will be obtained. From the results of the simulation also seem that high working gas temperatures reduces oscillation of the power output. the effect of the working gas volume does not significantly influence the output power. As for what can be concluded is, in the system that has been made, the main factor affecting the performance of the generating system is the temperature of the heating plate. So that performance optimization of the generating system can be further carried out in the parts related to these parameters.